Youth’s participation in the media and an analysis of the flow of information about them from one media platform to another - Vitković, Biljana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Active youth involvement in a community's daily life is the precondition for its development. The media are an important tool in securing that active involvement. An analysis of the younger generation’s presence across platforms further serves to gain a deeper understanding of the societal capacity for critical thinking and the level of general affinity to change. By conducting a one month long study of five informative TV programs, six daily newspapers (in printed form), two youth portals and the RTS (national public broadcaster) program listings, this paper aims to gain insight into the overall presence of young people in those media, and the topics which occupy them. Furthermore, the study aims to gain an understanding about the impact of a split representation of reality imposed by the selected media to the youth.Noticing the information overflowing from one media platform to another is of great importance, as it has an impact on the youth and their activism efforts, thus bearing a significant role in the studies conducted by the media and communication theory experts.Young people are making appearances in television broadcasting programs, having shows dedicated to them by the National public broadcaster (RTS) and are also publishing news on their active platform portals. Messages are being circulated, but there haven’t been any detailed, large-scale studies which can offer an answer to the question: what is the content of these messages, and if they circulate across the communicational space?The key contribution that this study aims to achieve is an attempt to answer these questions.The findings of this paper suggest that the communicational space of the youth towards the public is narrow, without any active communication channels, nor is there any information overflowing cross means of communication. The findings further indicate that the complexity and the solemnity of the content has shown to depend on the media which have created the content.Knowledge gained in this paper will serve as a starting point for further theoretical discussions, and a greater scope of media platforms selected to be included in future studies could lay the foundation for a work style reform of said media platforms.
Keywords: youth, the media, information, communication, communicational space, society, change, activism